Financial Frictions, Underinvestment, and Investment Composition : Evidence from Indian Corporates - Das, Sonali; Tulin, Volodymyr (Washington, D.C. : International Monetary Fund, 2017)
This paper studies private investment in India against the backdrop of a significant investment decline over the past decade. We analyze the potential causes of weaker investment at the firm level, using both firm-level financial statements and a novel dataset on firms' investment project decisions, and find that financial frictions have played a role in the slowdown. Firms with higher financial leverage invest less, as do firms with lower earnings relative to their interest expenses. Consistent with the notion of credit constraints leading to pro-cyclical investment, we also find that firms with higher leverage are (i) less likely to undertake new investment projects, (ii) less likely to complete investment projects once begun, and (iii) undertake shorter-term investment projects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet